Identification of Genes Involved in Bacteriostatic Antibiotic-Induced Persister Formation - Cui, Peng; Niu, Hongxia; Shi, Wanliang; Zhang, Shuo; Zhang, Wenhong; Zhang, Ying (Frontiers in Microbiology, 2018)
Persister cells are metabolically quiescent multi-drug tolerant fraction of a genetically sensitive bacterial population and are thought to be responsible for relapse of many persistent infections. Persisters can be formed naturally in the stationary phase culture, and, and also can be induced by bacteriostatic antibiotics. However, the molecular basis of bacteriostatic antibiotic induced persister formation is unknown. Here we established a bacteriostatic antibiotic induced persister model and screened the Escherichia coli single gene deletion mutant library for mutants with defect in rifampin or tetracycline induced persistence to ofloxacin. Thirsty-seven and 9nine genes were found with defects in rifampin- and tetracycline-induced persister formation, respectively. Six mutants were found to overlap in both rifampin and tetracycline induced persister screens: recA, recC, ruvA, uvrD, fis, and acrB. Interestingly, four of these mutants (recA, recC, ruvA and uvrD) mapped to DNA repair and recombination pathway, one mutant mapped to global transcriptional regulator (fis) and one to efflux (acrB). The stationary phase culture of the identified mutants and parent strain BW25113 were subjected to different antibiotics including ofloxacin, ampicillin, gentamicin, and stress conditions including starvation and acid pH 4.0. All the 6six mutants showed less tolerance to ofloxacin, but only some of them were more sensitive to other specific stress conditions. Complementation of the 6sixfive of the six common mutants restored the persister level to that of the parent strain in both stationary phase and also the static antibiotic- induced persistersconditions. In addition to the DNA repair pathways shared by both rifampin and tetracycline induced persisters, genes involved in rifampin-induced persisters map also to transporters, LPS biosynthesis, flagella biosynthesis, metabolism (folate and energy), and translation, and heat shock, etc. These findings suggest that persisters induced by static antibiotics or generated from stationary phase culturesby different ways may share common mechanisms or pathways andof survival, as well as specific pathways unique to certain static agents, and also shed new insight into the molecular basis for of static antibiotic induced antagonism of cidal antibiotics.